STRATEGI PENINGKATAN PENDAPATAN AGROINDUSTRI KERUPUK TEPUNG TAPIOKA DI KELURAHAN MANGLI KECAMATAN KALIWATES KABUPATEN JEMBER - Efie Fadjrijah Eka; Rizal Rizal; muksin muksin (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Jember economy has supported by two agricultural sectors which are food processing agrindustry and agriculture. One of raw materials agriculture processing product industries in Jember is crackers agroindustry. The production centre of this agroindustry is located at Mangli, Kaliwates sub district Jember. This research is analytic quantitative and qualitative analytic descriptive using SEM-PLS approach and helped by R Program that used to formulate factors model that having an effect on the income also using SWOT analysis to formulate the strategy. The results of this research showed that variables that having an effect on the level of income and cost efficiency of production at Mangli, Kaliwates sub district Jember are social factors, economy and the business strategy. Economically, the crackers industry at Mangli, Kaliwates sub-district, Jember is profitable with Rp. 112.560,47 per day and the efficient production fee with value R/C 1,06. The enhancement strategies of crackers industry are include : developing the strong partnership with raw materials supplier, the efficiency of crackers production, technology production adoption, market segment extension, the enhancement of capital access, enhancement of crackers product quality, and diversification of processed crackers product. Key words : crackers agroindustry,income, SEM-PLS, SWOT analysis